ANALISIS PERBEDAAN RETURN PORTOFOLIO BERDASARKAN MODEL INDEKS TUNGGAL DAN PORTOFOLIO RANDOM - Hariasih, Ni Putu Nonik; Wirama, I Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Portfolio analysis is important for investors as a basis to diversify stock to form the optimal portfolio. The optimal portfolio can be determined by the Single Index Model which  is simple and easy to operate. The purpose of this study was to obtain empirical evidence determining the difference of return portfolios using Portfolio Single Index Model and random. This study uses the company shares Kompas 100 Index on the period of  January 2014 as the population. The research sample are 93 stocks which are selected by purposive sampling. Then the 68 selected candidates stock of  portfolio which have specific criteria for Single Index Model have ERBi value greater than ERBi value on the cut off point. The data were analyzed by using different test Paired Samples T-Test. The results shows that there are differences in the determination of portfolio return using the Single Index Model and random portfolio, in which the use of Single Index Model may provide a higher return than the Random portfolios.
Keywords: expected return, risk, return portfolio, single index model, random portfolio